ANÁLISE DE TENSÕES INTERNAS EM SISTEMAS DE REVESTIMENTOS CERÂMICOS DE FACHADAS NO DISTRITO FEDERAL DEVIDO A CARREGAMENTOS TÉRMICOS UTILIZANDO MODELAGEM MEF 3D - Uchôa, João Carlos Barleta; Bezerra, Luciano Mendes; Brito, Marcus Alexandre Noronha de; Montandon Júnior, Antonio Carlos; Silva, Willian Taylor Matias (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Some regions of Brazil are subjected to thermal variations of such level where tensions generated by these loads lead to a low efficiency of ceramic tile systems on the facades. The Federal District is one of those regions where temperatures in some seasons outweigh the treated and established a rule. Because of that this work develops a model of a complete system 3D of a ceramic coating on the facade, with the adoption of physical characteristics and actual thermal conditions measured with support from the National Institute of Meteorologia- INMET, thus evaluating the spread of these tensions to long layers of this type of system the same way that its resistance to adhesion.